(untitled) (Research, Society and Development, 2020)
This article presents a reflection on Federal Law No. 10,639/03 and the teaching-learning process through history textbooks for the 6th Year of Elementary School II, adopted by the Municipal Elementary School Padre Francisco Rafael Fernandes between 2005 and 2014, located in the urban area of the municipality of São Fernando - RN. It highlights the role of the history textbook in the classroom, emphasizing the need for themes related to Afro-Brazilian culture according to the Curricular Guidelines of this Law. In this sense, this article aims to analyze the historical context of the History Textbook, seeking to understand how Afro-Brazilian and African History and Culture are treated in this pedagogical tool, seeing in it the possibility of developing quality teaching-learning. Therefore, we address the issue of the Textbook, although we recognize that it is a product based on market laws, it is above all an educational tool. As a corpus of analysis, we will deal with the following textbooks: New Critical History (Mario Furley Schmidt, Editora Nova Geração, 2002); Araribá Project (Editora Moderna, 2006); History: Society & Citizenship (Alfredo Boulos Júnior, Ftd Publishing House, 2009) and Radix Project: História (Cláudio Vicentino, Editora Scipione, 2012). As a result, we are still the product of a Eurocentric education, where there is the conscious and unconscious reproduction of prejudices that permeate our society.